Interactional Competences in Institutional Settings : From School to the Workplace - Pekarek Doehler, Simona; Bangerter, Adrian; de Weck, Geneviève; Filliettaz, Laurent; González-Martínez, Esther; Petitjean, Cécile (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This interdisciplinary volume brings together leading scholars from several disciplines to uncover the key to young people's socialization within institutional settings, from school to the workplace. Among the questions they consider are: what aspects of interactional competence are relevant for participation in practical activities within those settings? What are the interactional procedures through which diverse facets of interactional competence are recognized, legitimized and assessed in the course of practical activities? How do these procedures shape and reflect social institutions and people's understanding of them? The collection discusses interactional competences across a variety of institutional settings, and reflects on the institutional order by scrutinizing how such competences are interactionally treated within everyday institutional practices. The volume enriches an interdisciplinary understanding of fundamental concepts in the social sciences and will therefore be of interest to those working within linguistics, sociology, education, psychology of work, and speech therapy.